1987
DOI: 10.1002/j.1460-2075.1987.tb02371.x
|View full text |Cite
|
Sign up to set email alerts
|

Cell type-specificity elements of the immunoglobulin heavy chain gene enhancer.

Abstract: Communicated by W.Schaffner enhancer motifs analyzed are involved in positive rather than negative control of transcription.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
224
0

Year Published

1988
1988
1995
1995

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 260 publications
(235 citation statements)
references
References 60 publications
11
224
0
Order By: Relevance
“…In contrast, the O site is only important for tissue-specific enhancer function as mutations in O af fect enhancer function in B cells but not in fibroblasts (Lenardo et al 1987). In fact when the O site, in con junction with (xE4, is repeated tandemly, it can function as a tissue-specific enhancer (Gerster et al 1987). Fi nally, the sequences flanking the core enhancer are im portant for enhancer repression in inappropriate cells; deletion of these sequences allows the enhancer to func tion in fibroblasts (Imler et al 1987) or kidney cells (Kadesch et al 1986), or in T cells and macrophages as re ported here, even with a wild-type O site.…”
Section: Ig Heavy-chain Enhancer Regulationmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, the O site is only important for tissue-specific enhancer function as mutations in O af fect enhancer function in B cells but not in fibroblasts (Lenardo et al 1987). In fact when the O site, in con junction with (xE4, is repeated tandemly, it can function as a tissue-specific enhancer (Gerster et al 1987). Fi nally, the sequences flanking the core enhancer are im portant for enhancer repression in inappropriate cells; deletion of these sequences allows the enhancer to func tion in fibroblasts (Imler et al 1987) or kidney cells (Kadesch et al 1986), or in T cells and macrophages as re ported here, even with a wild-type O site.…”
Section: Ig Heavy-chain Enhancer Regulationmentioning
confidence: 99%
“…Factors that bind to the (xEl,|xE2,and |JLE3 are present in all cell types (Sen and Baltimore 1986a;Weinberger et al 1986;Lenardo et al 1987). In the case of the O site, at least two apparently distinct factors bind to the octamer (Landolfi et al 1986;Staudt et al 1986;Gerster et al 1987;Lenardo et al 1987), one of which is present only in lymphoid cells. On the basis of the discussion of the cis-acting require ments, this implies that this lymphoid-specific factor is important for positive enhancer function.…”
Section: Ig Heavy-chain Enhancer Regulationmentioning
confidence: 99%
See 1 more Smart Citation
“…In our laboratory we have shown the importance of two neighboring sequence motifs, namely the footprint motif number 4 (F4) and the octamer element, both of which are located within a 51-bp DdeI-Hinfl segment of the IgH enhancer [131]. .…”
Section: Protein Factors Binding To the Igh Enhancermentioning
confidence: 99%
“…This transcription factor interacts with the conserved octanucleotide 5'-ATGCAAAT-3', which is present in all known VH promoters and in the inverted orientation in the heavy-chain enhancer and all light-chain variable region gene promoters. In vivo and in vitro studies have shown that this element is the minimal requirement for efficient cell-type-specific transcription (4,8,11,13,15,18,25,29,34,48).Interestingly, a ubiquitous transcription factor, OTF1, mediates the transcription of the ubiquitously expressed histone H2B gene (43) and interacts with octanucleotide elements in small nuclear RNA gene promoters and the simian virus 40 enhancer (5). Both OTF1 (12) and OTF2 (39) have been purified, and the sequence of cloned OTF2 has * Corresponding author.…”
mentioning
confidence: 99%